Preparation method of silk fibroin-polydopamine water-based binder, silk fibroin-polydopamine water-based binder and application of silk fibroin-polydopamine water-based binder

By developing polydopamine-modified silk fibroin aqueous binder, the problem of infeasible cathode oxidation reaction and adhesive of sodium ion battery is solved, the bond strength and ionic conductivity of the battery are improved, and the circulation of the battery is improved. and rate performance.

CN119432318AActive Publication Date: 2025-02-14DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES

Patent Information

Application Number
CN202310963312.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-31
Publication Date
2025-02-14
Estimated Expiration
2043-07-31

AI Technical Summary

Technical Problem

The sodium ion battery cathode has a side oxidation reaction under high pressure, resulting in the degradation of the chemical structure of the electrolyte solution and the active material, and existing adhesives are not feasible in large-scale applications.

Method used

Develop a polydopamine-modified silk fibroin aqueous binder that removes sericin, dissolves and dialyses the silk fibroin in the silk cocoon, and then reacts with dopamine hydrochloride to form a water-soluble binder for sodium ions Preparation of the positive electrode of the battery.

Benefits of technology

The adhesive improves the bonding strength and ionic conductivity of the battery, improves the cycle performance and rate performance of the battery, extends the cycle life of the battery, and reduces the contamination and cost of using organic solvents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119432318A_ABST
    Figure CN119432318A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a silk fibroin-polydopamine water-based binder, the silk fibroin-polydopamine water-based binder and application of the silk fibroin-polydopamine water-based binder. The preparation method comprises the following steps: (1) removing sericin from silkworm cocoons by using a sodium carbonate solution, drying, and dissolving degummed silk by using a lithium bromide solution; (2) dialyzing the solution dissolved in the step (2), and freeze-drying I to obtain water-soluble silk fibroin; (3) dissolving the obtained water-soluble silk fibroin in water to obtain a silk fibroin solution; and (4) adding dopamine hydrochloride into the silk fibroin solution for reaction, and performing freeze drying II to obtain the silk fibroin-polydopamine water-based binder. The binder prepared by the invention can effectively improve the ionic conductivity of a positive electrode and the transmission efficiency of sodium ions, and effectively improve the cycle performance and rate capability of a battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a preparation method of a silk fibroin-polydopamine aqueous binder, a silk fibroin-polydopamine aqueous binder and an application thereof, and belongs to the technical field of battery materials. Background Art

[0002] As environmental issues and energy shortages intensify, large-scale energy storage systems (ESS) for sustainable and renewable energy sources such as solar and wind energy have received widespread attention. Lithium-ion batteries (LIBs) were commercialized in 1991, and the battery market has expanded rapidly, with applications diversifying from electronic devices to electric vehicles and stationary energy storage systems. However, the world's lithium resources are quite limited (~0.0065%), further increasing the cost of LIBs. Nowadays, sodium-ion batteries (SIBs) have attracted widespread attention due to their outstanding advantages, including highly abundant sodium resources in the earth's crust, low prices, and similar working principles to the dominant lithium-ion batteries, making SIBs the most likely LIB alternative for grid-scale energy storage.

[0003] The interface between the cathode and electrolyte solution undergoes secondary oxidation reactions under high pressure and becomes intrinsically unstable in SIBs. Secondary oxidation reactions can degrade the chemical structure of the electrolyte solution and the cathode active materials. The formation of a solid permeable interface (SPI) can passivate the cathode surface and prevent secondary oxidation reactions of the electrolyte solution. Although these surface films from different precursors can effectively passivate the surface to prevent degradation of the cathode and electrolyte solution, the thickness of these additives obviously hinders the Na + transfer, and further leads to poor rate capability. Moreover, these expensive and complicated methods are not feasible for large-scale applications. Therefore, it is highly desirable to form additive-free SPI for the cathode of SIBs. Few studies have focused on the feasibility of using binders to form SPI films for SIB cathodes. Binders are generally considered to be inactive ingredients that integrate active materials and conductive carbon on the current collector.

[0004] As the most commonly used binder in the past few decades, polyvinylidene fluoride (PVDF) has shown many advantages such as good electrochemical stability, binding ability, and high adhesion to active materials and current collectors. However, the toxic, volatile and flammable organic solvent N-methyl-2-pyrrolidone (NMP) is usually used to dissolve PVDF, and therefore, high drying temperatures are required to dry the high-boiling point NMP-based slurry. Since PVDF is an insulating polymer with low ionic conductivity, an additional high-energy barrier for sodium migration is introduced at the electrode / electrolyte interface and leads to deteriorated reaction kinetics. In addition, the weak van der Waals interaction between PVDF and the active materials, as well as the swelling / softening of PVDF in the electrolyte, make the electrode unstable and destroy the cycling stability. It has been reported that the mechanical toughness of the binder (e.g., alginate, carboxymethyl cellulose (CMC), pullulan, etc.) and the covalent and hydrogen bond formation between the surface oxides of the active materials and the polymer functional groups (e.g., polyacrylic acid (PAA), guar gum, and copolymers containing Meldrum acid) can be achieved. Mechanical toughness and bond formation are achieved by combining bond-forming PAA with mechanically tough polymers such as pectin, CMC, and pullulan. However, simply having strong binding ability is far from enough to solve the many problems of cathode materials related to reaction kinetics, interface stability, and composition stability. In addition, the cathode binder should also have electrochemical stability at high voltage. Therefore, there is an urgent need to develop a multifunctional binder.

[0005] Silk fibroin (SF) is a natural biodegradable protein fiber and a promising candidate material for electronic implants connected to the human body. The use of regenerated SF is based on the fact that it has the ability to capture or stabilize chemically or biologically active molecules, allowing new functions to be added. The main advantages of SF in batteries are its non-toxicity, mechanical flexibility, excellent thermal properties and suitable ionic conductivity. SF has begun to be used in various battery devices. For example, Yang Yu et al. (CN 111969206 A) prepared a silk fibroin-tannic acid aqueous binder for lithium-sulfur batteries to solve the problems of electrode integrity destruction and shuttle effect of sulfur electrodes during cycling. Similarly, Yang Yu et al. (CN 111961219 A) also designed a photo-crosslinked silk fibroin aqueous binder to solve the problems of poor adhesion of traditional binders and the shuttle effect of polysulfides. Summary of the invention

[0006] The present invention aims at the problems of low bonding strength and low ionic conductivity of positive electrode binders of sodium ion batteries, and invents a polydopamine-modified silk fibroin binder. The binder is an aqueous binder with good water solubility and can be evenly dispersed in the positive electrode slurry of sodium ion batteries. The high tensile strength and ductility of silk fibroin provide the binder with high adhesion and mechanical strength, which can enhance the bonding strength between active substances, conductive agents and current collectors and inhibit dendrite growth. In addition, silk fibroin can improve ionic conductivity and improve the cycle performance and rate performance of the battery. The modification of silk fibroin by dopamine can improve the bonding strength of the binder and the transmission efficiency of sodium ions.

[0007] According to one aspect of the present application, a method for preparing a silk fibroin-polydopamine aqueous binder is provided, the preparation method comprising the following steps:

[0008] (1) removing sericin from silk cocoons with a sodium carbonate solution, drying, and dissolving the degummed silk with a lithium bromide solution;

[0009] (2) dialyzing the solution dissolved in step (2), and freeze-drying I to obtain water-soluble silk fibroin;

[0010] (3) dissolving the obtained water-soluble silk fibroin in water to obtain a silk fibroin solution;

[0011] (4) adding dopamine hydrochloride to the silk fibroin solution and freeze-drying II to obtain the silk fibroin-polydopamine aqueous binder.

[0012] Optionally, the preparation method comprises the following steps:

[0013] (1) Preparation of water-soluble silk fibroin from silkworm cocoons:

[0014] Silk cocoons were cut and slurried in 0.02 M Na 2 CO 3 The solution was boiled to remove sericin. The degummed silk was placed in an oven to dry overnight, and the degummed silk was dissolved with a 9.3M LiBr solution at 60°C. The dissolved solution was poured into a dialysis membrane and dialyzed in ultrapure water for 3 days, with ultrapure water replaced every four hours. The conductivity of the liquid was measured by an ion conductivity meter to determine the degree of dialysis. After 3 days of dialysis, the pure silk fibroin solution was collected and frozen at -20°C in a refrigerator overnight, and then placed in a freeze dryer for freeze drying to obtain water-soluble silk fibroin;

[0015] (2) preparing a silk fibroin-polydopamine binder by modifying silk fibroin with dopamine hydrochloride;

[0016] Silk fibroin was dissolved in water to obtain a silk fibroin solution, which was modified by adding dopamine hydrochloride. The solution was stored in a refrigerator for 2 days, and spontaneous polymerization of polydopamine could be detected by the browning of the solution. Similarly, the solution was frozen at -20°C overnight and then freeze-dried in a freeze dryer to obtain a silk fibroin-polydopamine binder.

[0017] Optionally, in step (4), the concentration of dopamine hydrochloride in the silk fibroin solution is 0.2-1 mol / L.

[0018] Optionally, the concentration of dopamine hydrochloride in the silk fibroin solution is selected from any value among 0.2 mol / L, 0.3 mol / L, 0.5 mol / L, 0.7 mol / L, 1.0 mol / L or a range between any two of the above.

[0019] Optionally, the concentration of dopamine hydrochloride is 0.2-1 mol / L.

[0020] Optionally, the concentration of dopamine hydrochloride is selected from any value among 0.2 mol / L, 0.3 mol / L, 0.5 mol / L, 0.7 mol / L, 1.0 mol / L or a range between any two of the above.

[0021] Optionally, the concentration of the silk fibroin solution is 7% to 8wt%.

[0022] Optionally, the concentration of the silk fibroin solution is selected from any value of 7wt%, 7.2wt%, 7.4wt%, 7.5wt%, 7.8wt%, 8wt% or a range between any two of the above values.

[0023] Optionally, the mass volume ratio of the silkworm cocoon to the sodium carbonate solution is 1g:60mL-100mL.

[0024] Optionally, in step (1), the mass volume ratio of the silkworm cocoon to the lithium bromide solution is 1 g: 25 mL to 50 mL.

[0025] Optionally, the silk cocoons are boiled in a 0.02M sodium carbonate solution for 0.5 to 1 h.

[0026] Optionally, in step (1), the dissolution time in 9.3M lithium bromide solution is 4 to 6 hours.

[0027] Optionally, in step (1), the drying temperature is 60-80°C.

[0028] Optionally, the drying temperature is selected from any value of 60°C, 65°C, 70°C, 75°C, 80°C or a range between any two of the above values.

[0029] Optionally, the temperatures of freeze drying I and freeze drying II are independently selected from -20°C to -30°C.

[0030] According to another aspect of the present application, a silk fibroin-polydopamine aqueous binder prepared by the above-mentioned preparation method is provided.

[0031] Optionally, the silk fibroin-polydopamine aqueous binder is prepared from a mixture of silk fibroin and polydopamine, and has a network structure formed by carboxyl groups and ester groups.

[0032] According to another aspect of the present application, there is provided an application of the above-mentioned silk fibroin-polydopamine aqueous binder in a sodium ion battery electrode, and a method for preparing the sodium ion battery electrode comprises: grinding and coating a mixture containing the silk fibroin-polydopamine aqueous binder, an active material, and a conductive agent on a current collector, and drying to obtain the sodium ion battery electrode.

[0033] Optionally, the method for preparing the sodium ion battery electrode sheet comprises the following steps: mixing the sodium ion battery aqueous binder and active material to obtain a slurry, coating the slurry on the current collector to obtain a coating, and then sequentially drying the coating under normal pressure and vacuum drying to obtain a sodium ion battery electrode sheet, wherein the vacuum drying temperature is 80 to 120°C, preferably 80°C.

[0034] Optionally, the sodium ion battery electrode comprises a current collector and a coating coated on the current collector, wherein the coating comprises an active material, a conductive agent and a silk fibroin-polydopamine aqueous binder.

[0035] Optionally, the active material is selected from carbon-based materials, alloy materials, conversion materials, polyanion

[0036] At least one of a sub-compound and an organic material.

[0037] Optionally, the active material is a polyanion compound, and the polyanion compound is selected from at least one of sodium vanadium phosphate, sodium vanadium fluoride phosphate, and sodium iron phosphate.

[0038] Optionally, the active material is selected from one of carbon-based materials, alloy materials, conversion materials, polyanionic compounds, Prussian blue, organic materials

[0039] Optionally, the conductive agent is selected from at least one of carbon nanotubes, carbon fibers, graphene, acetylene black, Super P, and Super S.

[0040] Optionally, the current collector is at least one of aluminum foils.

[0041] Optionally, the mass ratio of the silk fibroin-polydopamine aqueous binder, the active material, and the conductive agent is: 10-3: 80-94: 10-3.

[0042] Optionally, the silk fibroin-polydopamine aqueous binder accounts for 5-20% of the mass of the mixture.

[0043] Optionally, the silk fibroin-polydopamine aqueous binder accounts for 5-10% of the mass of the mixture.

[0044] Optionally, the drying includes normal pressure drying and vacuum drying.

[0045] Optionally, the temperature of the normal pressure drying is 40 to 60° C., and the time of the normal pressure drying is 1 to 3 hours.

[0046] Optionally, the temperature of the normal pressure drying is selected from any value of 40°C, 45°C, 50°C, 55°C, 60°C or a range between any two of the above values.

[0047] Optionally, the normal pressure drying time is selected from any value of 1 h, 1.5 h, 2 h, 2.5 h, 3 h, or a range between any two of the above values.

[0048] Optionally, the vacuum drying temperature is 80-120° C., and the vacuum drying time is 8-16 hours.

[0049] Optionally, the vacuum drying temperature is selected from any value of 80°C, 90°C, 100°C, 110°C, 120°C or a range between any two of the above values.

[0050] Optionally, the vacuum drying time is selected from any value among 8h, 9h, 10h, 12h, 14h, 16h or a range between any two of the above.

[0051] The beneficial effects of this application include:

[0052] 1) The present application synthesizes a water-based binder and the preparation method is simple, green and environmentally friendly, with abundant resources, which can effectively reduce the pollution and cost problems caused by the use of organic solvents.

[0053] 2) The binder prepared in the present application can effectively improve the bonding strength of the battery binder, improve the uniformity of the positive electrode slurry, and enable the slurry to form a uniform film on the current collector, thereby effectively extending the cycle life of the battery.

[0054] 3) The binder prepared by the present invention can effectively improve the ionic conductivity of the positive electrode and the transmission efficiency of sodium ions, and effectively improve the cycle performance and rate performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 This is a comparison chart of the contact angles of the SFPDA adhesive film and the PVDF adhesive film for sodium ion battery electrolyte in this application.

[0056] Figure 2 This is a SEM image of the electrode plate cross section at 10 um of a sodium ion battery assembled with the positive electrode plate prepared in Example 1 of the present application after charge and discharge cycles.

[0057] Figure 3 This is a SEM image of the electrode piece cross section at 10 um of a sodium ion battery assembled with the positive electrode piece prepared in Comparative Example 1 of the present application after charge and discharge cycles.

[0058] Figure 4 The charge and discharge cycle performance test results of the sodium ion battery assembled with the positive electrode sheet prepared in Example 1 of the present application.

[0059] Figure 5 The charge and discharge cycle performance test results of the sodium ion battery assembled with the positive electrode sheet prepared in Comparative Example 1 of the present application.

[0060] Figure 6 This is a comparison chart of the cyclic voltammetry of the sodium ion battery assembled with the positive electrode sheets prepared in Example 1 of the present application and Comparative Example 1.

[0061] Figure 7 The charge and discharge rate performance test results of the sodium ion battery assembled with the positive electrode sheets prepared in Example 1 and Comparative Example 1 of the present application. DETAILED DESCRIPTION

[0062] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0063] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0064] This application uses the Neware battery testing system (Shenzhen, China) to test the electrochemical performance of sodium ion batteries.

[0065] The cyclic voltammetry test was carried out using a Chenhua electrochemical workstation.

[0066] The degree of dialysis is determined by measuring the conductivity of the fluid using an ion conductivity meter.

[0067] The preparation method of the silk fibroin-polydopamine aqueous binder comprises the following steps:

[0068] (1) Water-soluble silk fibroin was prepared from silkworm cocoons.

[0069] Silk cocoons were cut and slurried in 0.02 M Na 2 CO 3Boil the solution to remove sericin. Dry the degummed silk in an oven overnight. Dissolve the degummed silk with 9.3M LiBr solution at 60°C. Pour the dissolved solution into a dialysis membrane and dialyze in ultrapure water for 3 days, replacing the ultrapure water every four hours. The degree of dialysis is determined by measuring the conductivity of the liquid using an ion conductivity meter. Collect the pure silk fibroin solution after 3 days of dialysis. Freeze in a refrigerator at -20°C overnight, then place in a freeze dryer for freeze drying to obtain water-soluble silk fibroin.

[0070] (2) Silk fibroin was modified by dopamine hydrochloride to prepare silk fibroin-polydopamine binder.

[0071] Silk fibroin was dissolved in water to obtain a silk fibroin solution, which was modified by adding dopamine hydrochloride. The solution was stored in a refrigerator for 2 days, and spontaneous polymerization of polydopamine was detected by browning of the solution. Similarly, the silk fibroin-polydopamine binder was obtained by freeze drying in a freeze dryer after being frozen overnight at -20°C.

[0072] Example 1

[0073] 5 g of silk cocoons were cut and saturated with 300 mL of 0.02 M Na 2 CO 3 Boil the solution for 30 minutes to remove the sericin. Dry the degummed silk in an oven at 60°C overnight. Dissolve the degummed silk with 25mL of 9.3M LiBr solution. Stir at 60°C for 4h to dissolve the fibers into the LiBr solution. Pour the dissolved solution into a dialysis membrane and dialyze in ultrapure water for 3 days, replacing the ultrapure water every four hours. The degree of dialysis is determined by measuring the conductivity of the liquid using an ion conductivity meter. Collect the pure silk fibroin solution after 3 days of dialysis. Freeze in a refrigerator at -20°C overnight, then place in a freeze dryer for freeze drying to obtain water-soluble silk fibroin.

[0074] 0.75 g of silk fibroin was dissolved in 9.25 g of water to obtain a 7.5 wt% silk fibroin solution, which was modified by adding 0.35 g of 0.2 M dopamine hydrochloride at a final concentration. The solution was stored in a refrigerator for 2 days, and spontaneous polymerization of polydopamine was detected by browning of the solution. Similarly, the solution was frozen overnight at -20°C and then freeze-dried in a freeze dryer to obtain a silk fibroin-polydopamine binder (SFPDA).

[0075] Example 2

[0076] Sodium vanadium phosphate (NVP) is used as the positive electrode material, and the material synthesized in Example 1 is used as the binder. Weigh 40 mg of sodium vanadium phosphate positive electrode material, 5 mg of acetylene black and 5 mg of binder, dissolve and grind with deionized water to make pulp, and use the doctor blade method to evenly apply the electrode slurry on the current collector aluminum foil, and dry it in an oven at 60°C for 12 hours. Finally, use a cutting machine to cut out the pole pieces of the corresponding size to obtain the positive pole pieces of the sodium ion battery. The prepared positive pole pieces are moved into a glove box filled with argon and with a water content of less than 10ppm, weighed piece by piece, and recorded, and then assembled into a battery together with a glass fiber diaphragm, an electrolyte and a sodium negative electrode in the glove box to obtain a sodium ion battery; wherein 1.0 mol / L of sodium perchlorate is dissolved in a mixed solution of ethylene carbonate and diethyl carbonate (1:1 v / v, 5% fluoroethylene carbonate) as an electrolyte.

[0077] Comparative Example 1

[0078] Polyvinylidene fluoride (PVDF) binder is used to prepare the positive electrode plate and assemble the sodium ion battery.

[0079] The sodium ion batteries prepared in Example 2 and Comparative Example 1 were subjected to charge and discharge experiments. The specific experimental steps were as follows: the battery was subjected to constant current charge and discharge tests in the voltage range of 2.5-3.8V using a Neware battery test system (Shenzhen, China). The cyclic electrochemical cycle performance was investigated at a current density of 0.1C, and the electrochemical rate performance was investigated at a current density of 0.1C to 1C. The cyclic voltammetry test was performed using a Chenhua electrochemical workstation.

[0080] Figure 2 and Figure 3 The cross-sectional views of the pole pieces made with silk fibroin-polydopamine as a binder and polyvinylidene fluoride as a binder after charge and discharge cycles are shown. The active material and the aluminum foil current collector of the pole piece made with SFPDA as a binder are still tightly bonded after the cycle, while the pole piece made with PVDF as a binder has obvious cracks between the active material and the current collector after the cycle, and the cracking is serious.

[0081] Figure 1 is the contact angle of the electrolyte solution with SFPDA and PVDF membrane. The contact angle of the electrolyte solution with the SFPDA membrane is 40.44°. In contrast, the contact angle on PVDF is about 48.84°. According to previous reports, good electrolyte wettability is conducive to the penetration of electrolytes and promotes the rapid diffusion of ions at the solid / liquid interface. Therefore, as a battery binder, SFPDA has better adhesion and wettability than PVDF.

[0082] Figure 4The charge-discharge curve of the first five cycles of the positive electrode material prepared with silk fibroin-polydopamine as the binder at 0.1C shows a wide charge-discharge platform at around 3.4V. This is due to the V 4+ / V 3+ The specific capacity of NVP-SFPDA is 117.11 mAh g -1 . Figure 5 The charge-discharge curve of the first five cycles of the positive electrode material prepared with PVDF as the binder at 0.1C. The specific capacity of NVP-PVDF is 101.8 mAh g -1 .

[0083] Figure 6 This is the charge and discharge cycle performance curve of a sodium ion battery assembled with pole pieces prepared using SFPDA as a binder at 0.1C. After 50 cycles, the battery's discharge capacity is 108.93mAh / g, and its capacity retention rate is 92.5%.

[0084] Figure 7 The figure shows the charge and discharge rate performance of the battery assembled with the pole pieces prepared by the two binders. With the increase of current density, the rate performance of the silk fibroin-polydopamine binder is better than that of the PVDF binder in the range of 0.5-1C.

[0085] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for preparing a silk fibroin-polydopamine aqueous binder, characterized in that: The preparation method comprises the following steps: (1) removing sericin from silk cocoons with a sodium carbonate solution, drying, and dissolving the degummed silk with a lithium bromide solution; (2) dialyzing the solution dissolved in step (2), and freeze-drying I to obtain water-soluble silk fibroin; (3) dissolving the obtained water-soluble silk fibroin in water to obtain a silk fibroin solution; (4) adding dopamine hydrochloride to the silk fibroin solution and freeze-drying II to obtain the silk fibroin-polydopamine aqueous binder.

2. The preparation method according to claim 1, characterized in that: In the step (4), the concentration of dopamine hydrochloride in the silk fibroin solution is 0.2-1 mol / L; Preferably, the concentration of the silk fibroin solution is 7% to 8wt%.

3. The preparation method according to claim 1, characterized in that: The mass volume ratio of the silkworm cocoon to the sodium carbonate solution is 1g:60mL-100mL; Preferably, in step (1), the mass volume ratio of the silkworm cocoon to the lithium bromide solution is 1 g: 25 mL to 50 mL.

4. The preparation method according to claim 1, characterized in that: The silk cocoons are boiled in a 0.02M sodium carbonate solution for 0.5 to 1 h; Preferably, in step (1), the dissolution time in 9.3 M lithium bromide solution is 4 to 6 hours.

5. The preparation method according to claim 1, characterized in that: In the step (1), the drying temperature is 60 to 80°C; Preferably, the temperatures of freeze drying I and freeze drying II are independently selected from -20°C to -30°C.

6. A silk fibroin-polydopamine aqueous binder prepared by the preparation method according to any one of claims 1 to 5.

7. Use of the silk fibroin-polydopamine aqueous binder according to claim 6 in sodium ion battery electrodes, characterized in that: The preparation method of the sodium ion battery electrode comprises: grinding and coating a mixture containing a silk fibroin-polydopamine aqueous binder, an active material and a conductive agent on a current collector, and drying the mixture to obtain the sodium ion battery electrode.

8. The use according to claim 7, characterized in that: The active material is selected from at least one of carbon-based materials, alloy materials, conversion materials, polyanion compounds, and organic materials; Preferably, the active material is a polyanion compound, and the polyanion compound is selected from at least one of sodium vanadium phosphate, sodium vanadium phosphate fluoride, and sodium iron phosphate; Preferably, the conductive agent is selected from at least one of carbon nanotubes, carbon fibers, graphene, acetylene black, Super P, and Super S; Preferably, the current collector is aluminum foil.

9. The use according to claim 7, characterized in that: The mass ratio of the silk fibroin-polydopamine aqueous binder, the active material, and the conductive agent is: 10-3: 80-94: 10-3; Preferably, the silk fibroin-polydopamine aqueous binder accounts for 5 to 20% of the mass of the mixture; Preferably, the silk fibroin-polydopamine aqueous binder accounts for 5-10% of the mass of the mixture.

10. The use according to claim 7, characterized in that: The drying includes normal pressure drying and vacuum drying; Preferably, the temperature of the atmospheric pressure drying is 40 to 60° C., and the atmospheric pressure drying time is 1 to 3 hours; Preferably, the vacuum drying temperature is 80-120° C., and the vacuum drying time is 8-16 hours.

Citation Information

Patent Citations

  • Photo-crosslinking silk fibroin water-based binder as well as preparation method and application thereof

    CN111961219A

  • Water-based adhesive and application thereof in lithium ion battery

    CN111969206A

  • Preparation method of dopamine-regulated natural silk fibroin microfiber

    CN109403046A

  • Composite gel based on silk fibroin and polydopamine as well as preparation method and application of composite gel

    CN112574436A

  • Hyaluronic acid / silk fibroin double-crosslinking injectable hydrogel and preparation method thereof

    CN114601958A

Cited By

  • Rapid curing biological adhesive based on photo-crosslinking regenerated silk fibroin-polydopamine composite material as well as preparation method and application of rapid curing biological adhesive

    CN121718312A